Medical Waste Management Practices in Sylhet City among Healthcare Providers (Medicine Today, 2023)
Introduction: In the present world, large amount of wastes are clinical wastes, generated during diagnosis, treatment and research purpose. Most of the clinical wastes are hazardous like infectious, toxic of radioactive compounds. It is challenging to ensure proper waste management for developing countries like Bangladesh.Materials and Methods: This cross sectional study was conducted among doctors, nurse, nursing assistants, OT technicians, janitors, helper, sanitary worker and security guards at different private hospitals, clinics and diagnostic centers in Sylhet city. 300 healthcare staffs were purposively interviewed to evaluate the extend practices of biological or hospital waste management from January 2021 to December 2021. The study was conducted after taking informed written consent.Results: The outcomes of the present study indicated that maximum of the study participants were knowledgeable. But majority (71%) still do not use PPE (Personal protective equipment), 53% were not immunized against hepatitis B. They also had less practice to keep the hospital wastes in correct color coded container and less practice of washing the waste container properly.Conclusion: Most participants valued the significance of waste management practice to prevent health hazards but average practice was observed among them. For proper waste handling and disposal, frequent awareness program should be conducted among the health personnel.Medicine Today 2023 Vol.35(1): 12-15